ROLE OF THE SMALL BUSINESS IN SHAPING RUSSIA'S INNOVATION POTENTIAL - O. Demenko (Вестник университета)
The article describes about the relevance of small enterprises in the formation of an innovative economy, about the need to construct innovative infrastructure. Data distribution of Russian small businesses by function.